Perceptions and Practices of Sharia-Based Finance in Post-Pandemic MSMEs: A Qualitative Study in Urban-Rural Areas - Nur Ela; Oxy Hendro Prabowo; Muhammad Fadil Himawan; Aldo Hermaya Aditya Nur Karsa (Journal of Village Development Innovation, 2025)
The COVID-19 pandemic has affected the financial stability of MSMEs in Indonesia, especially in terms of financial management and access to financing. In the context of post-pandemic economic recovery, sharia-based financial systems are gaining traction as a more ethical and sustainable alternative. This study aims to explore the perceptions and practices of MSMEs towards Islamic finance, by comparing the dynamics in urban and rural areas. This research uses a qualitative approach with a phenomenological method. Informants were purposively selected from MSME players who have used or been exposed to Islamic financial services. Data collection techniques were conducted through in-depth interviews and field observations, and analyzed using the Miles and Huberman thematic model. The results showed that urban MSME players have a higher understanding of sharia principles and are more active in utilizing Islamic financial products, such as murabaha financing and Islamic savings. In contrast, rural MSME players rely more on informal systems based on community trust, and face more access barriers. Differences in motivation, literacy and social context are key factors that influence financial behavior in both regions. In conclusion, Islamic financial inclusion among MSMEs requires a participatory and contextual approach, taking into account local characteristics and structural challenges faced by businesses.